The Influence of Work Discipline and Compensation on Employee Performance at Perumda Tirta Pakuan Bogor City - Malda, Muhammad; Samsuri; Ismartaya (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2024)
Employee performance is an important part of employees to achieve and support company goals. Work discipline and compensation have an impact on employee performance, so companies should pay attention to these things. Questionnaires were distributed to 40 respondents using a quantitative approach, descriptive and verification research types and using surveys. The questionnaire uses validity tests, reliability tests and classical assumption tests. Research data analysis includes multiple linear regression analysis. The results of the research show that simultaneously and partially the all variables have a positive and significant effect on the performance of PDAM Tirta Pakuan Bogor City employees